(untitled) (Eurasian Journal of Learning and Academic Teaching, 2025)
The productivity and sorting of the teacher classroom is the potential for the quality of knowledge and the ability to apply the theoretical and practical knowledge in this process. Improving the quality and efficiency of the educational process depends in many cases, which is provided with educational tools and how to use educational techniques.Scientific principles are approved in practice based on the effective conduct of laboratory work on the basis of virtual developments, on the basis of pedagogical and research conducted as a physical practacter